2018
DOI: 10.1042/bcj20170703
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein protects cardiomyocytes against necrosis induced by oxygen and glucose deprivation through SR-B1, PI3K, and AKT1 and 2

Abstract: The cardioprotective lipoprotein HDL (high-density lipoprotein) prevents myocardial infarction and cardiomyocyte death due to ischemia/reperfusion injury. The scavenger receptor class B, type 1 (SR-B1) is a high-affinity HDL receptor and has been shown to mediate HDL-dependent lipid transport as well as signaling in a variety of different cell types. The contribution of SR-B1 in cardiomyocytes to the protective effects of HDL on cardiomyocyte survival following ischemia has not yet been studied. Here, we use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Not surprisingly, the absence of PDZK1 did not permit the athero-protective effects of HDL against apoptosis, highlighting the importance of PDZK1 in mediating HDL signalling in macrophages. Consistently, in another study by this group earlier this year [11], they showed that HDL signalling via SR-BI and Akt protected cardiomyocyte necrosis in response to oxygen and glucose deprivation in vitro.…”
supporting
confidence: 75%
“…Not surprisingly, the absence of PDZK1 did not permit the athero-protective effects of HDL against apoptosis, highlighting the importance of PDZK1 in mediating HDL signalling in macrophages. Consistently, in another study by this group earlier this year [11], they showed that HDL signalling via SR-BI and Akt protected cardiomyocyte necrosis in response to oxygen and glucose deprivation in vitro.…”
supporting
confidence: 75%
“…While our analysis of HDL modification was limited to detection of protein cross‐linking, it is possible that some reactive aldehydes preferentially modify nonprotein components of HDL. Additionally, the majority of our studies was performed using primary peritoneal macrophages that were isolated from mice 4 days postinjection with 4% thioglycolate, a model system that has been routinely used for studies of lipoprotein metabolism . We chose thioglycolate‐elicited macrophages for our studies for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Durham et al [ 19 ] demonstrated that HDLs protect cardiomyocytes against necrosis induced by oxygen and glucose deprivation via a mechanism involving scavenger receptor class B, type 1 (SR-BI). HDL treatment resulted in the phosphorylation of protein kinase B (Akt) in cardiomyocytes in SR-BI +/+ cardiomyocytes, but not in SR-BI −/− cardiomyocytes.…”
Section: Biological Mechanisms That May Contribute To the Beneficimentioning
confidence: 99%